Analysis of Physical Education Classes in a Brazilian Public School - Hammes, Lúcio Jorge; Armas Carvalho, Lisiane Teixeira de; Selau, Bento (Advances in Social Sciences Research Journal, 2018)
This study aimed at analyzing Physical Education classes in the first years of an Elementary School located in an outlying ghetto in a Brazilian city. The methodological proposal was relational psychomotricity, intended for evaluating whether it enables the development of students imitative activity. Regarding methodology, it was a pedagogical intervention whose data collection tools were observation and a focus group. Its subjects were children attending the first years in Elementary School. Results showed that the proposal of relational psychomotricity was appropriate to the pedagogical work carried out by the reference teacher with children attending these classes. Despite teacher interventions, imitation emerged in free activities throughout the play time, enabling an increase in the imitative activity.